HEALTH LITERACY AND FOOD SECURITY FROM A GENDER PERSPECTIVE: ANALYSES OF WOMEN’S RESILIENCE IN SEMI-ARID REGIONS - Roberto Ramos, Paulo; Miryam da Silva Alves, Maria; Neves Araújo, Herácliton; Gabriela Alves de Oliveira, Juliana; Wesley Costa Dias, Jonathan; Almeida Ferreira, Rodrigo; Eliete Ribeiro de Araújo, Maria; Alencar da Silva, Robismar; Ribeiro Galvão Filho, Raimundo; Alan Barbosa Bispo, Italo; da Silva Gomes, Tatiana; Paulo da Cunha, Pedro; et al. (Revista Gênero e Interdisciplinaridade, 2026)
This article examines the relationship between health literacy, food security, and gender in semi-arid regions, addressing the problem that most studies on food insecurity emphasize only food shortages or income deficits, neglecting the role of household knowledge in survival strategies. The main objective was to analyze how levels of health literacy among women living in semi-arid contexts influence coping strategies against food and nutrition insecurity under water scarcity conditions. An integrative literature review was conducted between October 2025 and January 2026 across international and regional databases, starting with 216 records and applying predefined thematic and methodological criteria, followed by reflexive thematic analysis. Results showed that women’s food and water literacy functions as an invisible infrastructure of food security, linking dietary substitution, home gardens, solidarity networks, and household water management. Evidence indicates that policies focused solely on income and production overlook these cognitive and territorial dimensions. The study concludes that food security in semi-arid regions depends on territorialized knowledge and women’s adaptive capacities, and that public policies should incorporate contextualized food education, support for rural women, and socio-ecological integration in managing scarcity.